Selective Catalytic Aerobic Photooxidation of Thioethers to Sulfoxides - Ji, Wan-Sheng; Li, Xiao-Long; Huang, Qiu-Shan; Xu, Jin-Bu; Li, Xiaohuan; Gao, Feng (Synlett, 2025)
A convenient visible-light-promoted oxidation of thioethers to sulfoxides is developed utilizing eosin Y as the photocatalyst and molecular oxygen from air as the oxidant. This photochemical protocol features good functional group tolerance and excellent chemoselectivity. Under the developed mild conditions, a wide variety of sulfides are converted into the corresponding sulfoxides in excellent yields (up to 93%). Moreover, this protocol can easily be amplified to gram scale, showing good practical value.
Keywords: photocatalysis; oxidation; eosin Y; sulfoxides; thioethers